Systematic review and meta-analysis of endoscopic ablative treatment of Barrett’s esophagus - Ferreira De Souza, Thiago (2017)
Background: Barrett’s esophagus (BE) is the main risk factor for esophageal adenocarcinoma. Its therapeutic approach is controversial and surgical treatment in the presence of high-grade intraepithelial neoplasia may be indicated. Endoscopic approach is an alternative with lower mortality and morbidity rates and favorable results. Objective: To define the best option, according to literature, to treat Barrett’s Esophagus. Materials and methods: Design: Systematic review of PUBMED, EMBASE, LILACS, and Cochrane Library databases was conducted and articles of randomized, controlled studies on BE endoscopic ablative treatment were selected. The systematic review through PUBMED retrieved results with higher evidence level and available recommendation grade regarding BE ablative therapy. Nine articles on randomized, controlled studies classified as A or B according to the Oxford table were selected. Cryotherapy, laser, photodynamic therapy (PDT), multipolar electrocoagulation (MPEC), and ablation through argon plasma coagulation (APC) and radiofrequency were considered ablation therapies. Patients: 649 patients from 10 different studies were analysed. Results: PDT was found to present an increase in treatment failure compared with APC, NNH = -7. BE ablation through MPEC or APC was found to have similar risk for treatment failure in meta-analysis. PDT associated with proton pump inhibitor (PPI) is beneficial for BE ablation regarding PPI use alone, NNT = 2. Radiofrequency with PPI is an efficient method to reduce risk of treatment failure, NNT = 1. Conclusions: There are no studies demonstrating the benefit of indicating cryotherapy or laser therapy for BE endoscopic approach. APC ablation was found to have superior efficacy compared with PDT and ablation through APC and MPEC was found to present effective, similar results. Radiofrequency is the most recent approach requiring comparative studies for indication.